KERAGAMAN BAHASA DAN KESEPAKATAN MASYARAKAT: PLURALITAS DAN KOMUNIKASI - James T. Collins (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2014)
Indonesia has many cultures. One look through the diversity of Indonesian culture, which is one of the region is Maros, South Sulawesi. In addition, Indonesia is also renowned as one of the nation that has a high enough rank of complexity. Indonesian complexity appears in profile in Indonesian language. This article will look at the diversity of Indonesian based on ancient human migration patterns in the archipelago. In addition, it will also be reviewed on the role of the only language that has managed to unite the cultural diversity of ethnicity, and languages in Indonesia. The existence of a national language in Indonesia only because of the already established agreements among Indonesian people to their social ties. The agreement occurred cumulatively. Many factors affect the diversity of languages that exist in Indonesia. Among the factors that generate the linguistic diversity is a factor of two ancient human migration, the migration of Austronesian and Australo-Melanesian. Two current distribution of the prehistoric human remains influential in the formation of culture and language in the archipelago until now. All indigenous languages in Indonesia generated from two groups of ancient languages, the Austronesian language family and the Papuan languages family. Austronesian language family moved in the archipelago around 4,000 years ago. Meanwhile, Papuan language families move in the archipelago since 40,000 years ago. Thus it can be said that the diversity of language in contemporary Indonesia should be associated with the migration factor and several other factors. Other factors, among others, such as migration, the geography of the archipelago with many islands and mountains, and social factors and communication. Seeing these things, it can also noted that Indonesia has a very diverse languages. Unlike delivered Indonesia has only two varieties in language, namely formal and non-formal varieties. It would be flawed if it still considers Indonesian has only two varieties from the 250 speakers.